Recursos intangíveis de uma empresa de tecnologia sob a perspectiva da análise de redes organizacionais - Schleder, Marcus Vinicius Nascimento (2023)
Intangible assets increasingly influence the market value of organizations (IAZZOLINO and PIETRANTONIO, 2005), since the uniqueness of these resources directly interferes with their economic power (DRUCKER, 1993; LÉVY and AUTHIER, 1995; BROOKING, 1996; NONAKA and TAKEUSHI, 2006, QUINN, 1992; DE CARVALHO, 1999; SVEIBY, 1998) and value proposition (BARNEY, 2001; PENROSE, 1995). However, while intangible assets highlight the differentiation and competitive advantages of organizations, they also pose the challenge to the market of finding new ways of evaluating their performance and influencing results (KAYO et al., 2006). The Audit of Intangible Resources is an analysis methodology for environments in constant evolution, which considers the concepts of dynamic capabilities, in which a network perspective promotes their understanding (UJWARY-GIL, 2020). The dynamic aspects of the audit are enhanced by the inclusion of Organizational Network Analysis instruments, which allow diagnosing the interrelationships between the various objects of analysis, which are not isolated actors, but the interdependent relationships in the organizational context (BORGATTI, EVERETT and JOHNSON, 2018). It is noteworthy that in the knowledge-based economy, intangible resources are crucial for growth and increased organizational competitiveness (CRICELLI and GRIMALDI, 2008; MORGAN et al., 2019). For organizations structured around Information Technology, knowing computer resources or information assets is the basis for an environment where knowledge can flow safely and reliably (PEREIRA et al., 2016; BREWER et al., 2018). This study aimed to analyze the network of information, knowledge and task resources in the Voalle Group and identify their relationship with organizational objectives and value creation, through the Audit of Intangible Resources. In order to achieve the main objective, an analysis of the external environment, the organization's strategic objectives, value creation model and main business processes was carried out, to identify the organization's intangible resources and their relationships in networks of information resources, knowledge and tasks and analysis of the relationship between intangible resources and organizational objectives and value creation. Among the results found, less than half of the possible relationships in each network stood out, exposing a great opportunity for improvement in this regard. It was demonstrated, they demonstrate the high qualification of the actors, as well as the high capacity of the company to provide them with the necessary resources, despite this, an environment of little exchange of knowledge and poor relationships for working together was observed. The presence of clusters of groups of people stood out, creating islands of knowledge and communication, isolated from the rest of the organization. Important levels of resource and task redundancy were found, which offers some flexibility in case one or more employees leave the company. Access and use of resources are also high, indicating good infrastructure support by employees. In addition, they have a very solid knowledge base.